Tracking coverage, dropout and multidimensional equity gaps in immunisation systems in West Africa, 2000–2017. Issue 5 (September 2019) - Wariri, Oghenebrume; Edem, Bassey; Nkereuwem, Esin; Nkereuwem, Oluwatosin O; Umeh, Gregory; Clark, Ed; Idoko, Olubukola T; Nomhwange, Terna; Kampmann, Beate
Abstract : Background: Several West African countries are unlikely to achieve the recommended Global Vaccine Action Plan (GVAP) immunisation coverage and dropout targets in a landscape beset with entrenched intra-country equity gaps in immunisation. Our aim was to assess and compare the immunisation coverage, dropout and equity gaps across 15 West African countries between 2000 and 2017. Methods: We compared Bacille Calmette Guerin (BCG) and the third dose of diphtheria–tetanus–pertussis (DTP3) containing vaccine coverage between 2000 and 2017 using the WHO and Unicef Estimates of National Immunisation Coverage for 15 West African countries. Estimated subregional median and weighted average coverages, and dropout (DTP1–DTP3) were tracked against the GVAP targets of ≥90% coverage (BCG and DTP3), and ≤10% dropouts. Equity gaps in immunisation were assessed using the latest disaggregated national health survey immunisation data. Results: The weighted average subregional BCG coverage was 60.7% in 2000, peaked at 83.2% in 2009 and was 65.7% in 2017. The weighted average DTP3 coverage was 42.3% in 2000, peaked at 70.3% in 2009 and was 61.5% in 2017. As of 2017, 46.7% of countries (7/15) had met the GVAP targets on DTP3 coverage. Average weighted subregional immunisation dropouts consistently reduced from 16.4% in 2000 to 7.4% in 2017, meeting the GVAP target in 2008. In most countries, inequalities in BCG, and DTP3 coverage and dropouts were mainly related to equity gaps of more than 20% points between the wealthiest and the poorest, high coverage regions and low coverage regions, and between children of mothers with at least secondary education and those with no formal education. A child's sex and place of residence (urban or rural) minimally determined equity gaps. Conclusions: The West African subregion made progress between 2000 and 2017 in ensuring that its children utilised immunisation services, however, wide equity gaps persist.